Technique for measurement of fluorescence lifetime by use of stroboscopic excitation and continuous-wave detection. - Matthews, DR; Summers, H; Njoh, K; Errington, R; Smith, P; Barber, P; Ameer-Beg, S; Vojnovic, B (Optical Society of American (OSA), 2006)
A study of the practicality a simple technique for obtaining time-domain information that uses continuous wave detection of fluorescence is presented. We show that this technique has potential for use in assays for which a change in the lifetime of an indicator occurs in reaction to an analyte, in fluorescence resonance energy transfer, for example, and could be particularly important when one is carrying out such measurements in the scaled-down environment of a lab on a chip (biochip). A rate-equation model is presented that allows an objective analysis to be made of the relative importance of the key measurement parameters: optical saturation of the fluorophore and period of the excitation pulse. An experimental demonstration of the technique that uses a cuvette-based analysis of a carbocyanine dye and for which the excitation source is a 650 nm wavelength, self-pulsing AlGaInP laser diode is compared with the model.